How citizenship matters (or not): the citizenship–belonging nexus explored among residents in Oslo, Norway. Issue 7 (3rd October 2018) - Erdal, Marta Bivand; Doeland, Elin Martine; Tellander, Ebba
ABSTRACT: This article sheds light on what citizenship means for individuals' experiences of belonging. Through 41 interviews conducted in Oslo, Norway, we trace understandings of how, when and why citizenship matters (or not) for belonging. Our interviewees fall into one of four categories: born citizens; naturalized citizens; dual citizens and non-Norwegian citizens who would qualify for naturalization, thus mixing participants with and without immigrant backgrounds. We interpret individuals' experiences evaluating whether formal citizenship is explicitly or implicitly salient and whether it is associated with secure or insecure belonging. We find that citizenship matters for security and recognition, both linked to belonging, in expected and unexpected ways. Our findings point to how, when and why citizenship matters (or not) for belonging, constituting the citizenship–belonging nexus. Here, race continues to matter, as does the materiality of the passport document, in how the citizenship–belonging nexus interacts with the nation as locus of membership for citizens.